2021
DOI: 10.3390/asi4030057
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and Electromechanical Characteristics of Porous Poly(Ethylene-co-Vinyl Acetate) Copolymer Films for Smart Sensors and Mechanical Energy Harvesting Applications

Abstract: This paper investigates energy harvesting performances of porous piezoelectric polymer films to collect electrical energy from vibrations and power various sensors. The influence of void content on the elastic matrix, dielectric, electrical, and mechanical properties of porous piezoelectric polymer films produced from available commercial poly(ethylene-co-vinyl acetate) using an industrially applicable melt-state extrusion method (EVA) were examined and discussed. Electrical and mechanical characterization sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The different porosity of the dense CNF and the porous pulp films could be another explanation. However, it was reported that porosity in both inorganic and polymeric films generally increases the piezoelectric response [ 61 , 62 , 63 ], including in cellulose aerogels [ 16 ]. It was reasoned that the internal voids enhance the strain on the crystal structure and thereby increase the piezoelectricity.…”
Section: Resultsmentioning
confidence: 99%
“…The different porosity of the dense CNF and the porous pulp films could be another explanation. However, it was reported that porosity in both inorganic and polymeric films generally increases the piezoelectric response [ 61 , 62 , 63 ], including in cellulose aerogels [ 16 ]. It was reasoned that the internal voids enhance the strain on the crystal structure and thereby increase the piezoelectricity.…”
Section: Resultsmentioning
confidence: 99%
“…7. The equivalent circuit of a piezoelectric material [35,36] The rectifier stage, was composed by the diodes bridge made by diodes with reference 1N5817, and capacitance = 10µF.…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…The use of chitosan films in composite applications has the potential to enhance the mechanical and thermal properties of the composite, making it more resilient and reliable. Therefore, understanding the mechanical and thermal properties of chitosan films is critical in developing sustainable and efficient composite materials for various industrial applications [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%